Design and Development of a Motorized Electronic Valve as a Flow Control Actuator Based on the ESP32 Microcontroller - Nurkamila, Hasna Azkiya; Ridwan; Nur Jamiludin Ramadhan (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2026)
Electric actuators have an important role in automatic control systems by replacing manual mechanisms, therefore increasing efficiency through automation. Among the most expensive components in control systems are control valves. In this study, an electronically motorized valve was designed to respond to three types of industrial analog signals. The valve was developed using an ESP32 microcontroller to optimize the performance of the DC motor. The researched methodology followed the VDI 2206 model, which provides a systematic and structured approach to product development through modeling, analysis, and verification. The system is designed to integrate with PLC control using voltage and current signals as inputs. Validation results show that the system achieves multi-input capability with highly linear and accurate position control (R² > 0.99; MAPE 5.96%). Although the functional response to flow rate is also consistent (R² > 0.96), its accuracy is lower (MAPE 24.54%) due to systematic errors primarily caused by mechanical factors such as valve friction and pump pressure.